Lean in the classroom : the powerful strategy for improving student performance and developing efficient processes - Wiegel, Vincent (Routledge/Productivity Press, 2020)
The current way of organizing education is not tenable in the coming decade. We need to address how we teach, how we organize schools, how we increase the effectiveness of learning, how we construct classrooms, and how we deploy new technologies. Lean management philosophy has been successfully applied across many industries - from manufacturing to healthcare, financial services, and construction. Recently, interest in Lean has steadily increased in the education sector, as it was originally introduced in that area's administrative and support processes. Currently, the introduction of Lean and its potential in education is gaining wider exposure because of massive looming changes - for example, the introduction of technology in education (as EdTech within the traditional system and as MOOCs), demographic changes, budget pressure, new pedagogies, the entrance of more and more private providers, and changing demands of society and industry on the curriculum. What is missing is a joint framework that will allow schools, teachers, directors, and boards to harness the potential of these developments and then execute a strategy. Lean Education (LE) offers the potential to streamline the execution of strategy and teaching. It accelerates the development of new courses and studies that are closely aligned to the needs of students. It supports the integration of new technologies without overburdening teachers and staff. Lean in the Classroom brings all these elements together into a coherent framework so schools can make necessary changes in one concerted effort. Teaching, professional support, managing the daily work, and changing the way schools function are brought together as a schoolwide strategy to organize learning in a way that serves our students by making the most of their talents. This book is the first to define LE in all its aspects: course design, actual teaching and learning processes, school management, and the organization of supporting processes. It is firmly based on the Lean management philosophy in conjunction with pedagogy. The book draws on both scientific research in the field of Lean management in general and Lean education in particular. In addition, it is predicated on many years of hands-on experience applying Lean both inside and outside the education sector.- Resumé vydavatel
Keywords: vzdělávání; filozofie; studium a výuka; education; philosophy; study and teaching; elektronické knihy; monografie; electronic books; monographs